WORD OF MOUTH RELATIONSHIP ANALYSIS ON PURCHASE INTENTION AND ITS IMPACT ON PURCHASE DECISIONS - Dicky Apdillah; Riyan Fiqri Hidayat; Chairanda Al Azmi; Ahmad Zuwandana (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to analyze the relationship of Word of Mouth in Purchase Intention toward Purchase Decision. This study is a quantitative study using SEM PLS. The sample in this study was 100 respondents to consumers of Alfamart Kramat Pulo 2 with a non-probability sampling technique, namely a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a member of the sample. The data the analyzed using validity test and hypothesis test to obtain the result. The finding reveals that by empirical analysis, word of mouth has a statistically significant positive impact on purchasing interest, such that as word of mouth improves, so does purchasing intention. Meanwhile, in empirical evidence, purchasing intention has a positive and significant impact on purchasing decisions, such that if the purchasing interest in a product becomes increasingly attached to the minds of customers, the likelihood of making a purchase increases. Furthermore, according to empirical research, word of mouth has a positive and statistically significant impact on purchasing decisions.